Kozmološke simulacije nastanka galaksij - Kovač, Rok (Matrika, 2024)
This work serves as an overview of various cosmological simulations of galaxy formation and the methods used by these simulations. In the introduction, article describes the discovery of other galaxies and the expansion of the universe and the consequent birth of cosmology. It presents the importance of simulations for this field of astrophysics and various ways in which research groups deal with a huge number of particles and many processes they have to describe as efficiently as possible. It explains the basic structure of cosmological simulations: cosmological model, initial conditions and key ingredients such as baryonic matter, dark matter, and dark energy. For clarity, the article also presents a simple example on dark matter and in the conclusion it states the results of cosmological simulations to date and the goals of future simulations we have yet to achieve.
Keywords: cosmology; dark matter; galaxy formation; kozmologija; nastanek galaksij; simulacije; simulations; temna snov